Transforming the future of health together: The Learning Health Systems Consensus Action Plan. Issue 3 (25th April 2018) - Rubin, Joshua C.; Silverstein, Jonathan C.; Friedman, Charles P.; Kush, Rebecca D.; Anderson, W. Holt; Lichter, Allen S.; Humphreys, Darin J.; Brown, Jeffrey; Crawford, Laura; Walker, James M.; Tannen, Richard L.; Berry, Kate; et al.
Abstract: The Learning Health Community is an emergent global multistakeholder grassroots incipient movement bonded together by a set of consensus Core Values Underlying a National‐Scale Person‐Centered Continuous Learning Health System developed at the 2012 Learning Health System (LHS) Summit. The Learning Health Community's Second LHS Summit was convened on December 8 to 9, 2016 building upon LHS efforts taking shape in order to achieve consensus on actions that, if taken, will advance LHSs and the LHS vision from what remain appealing concepts to a working reality for improving the health of individuals and populations globally. An iterative half‐year collaborative revision process following the Second LHS Summit led to the development of the Learning Health Systems Consensus Action Plan .